2017
DOI: 10.1002/adom.201700276
|View full text |Cite
|
Sign up to set email alerts
|

Controlled Pinning of Conjugated Polymer Spherulites and Its Application in Detectors

Abstract: is of great interest because of their impact on mechanical, and functional properties, including thermal conductivity, [1] charge carrier mobility, [2][3][4][5][6][7] and electrical conductivity. [8,9] In addition, for suitable macroscopic polymer chain arrangements, polarized absorption and emission can be observed. [10] As a consequence, a variety of methods have been developed to manipulate and control the microstructure and the orientation of conjugated polymers. [11] Some of these methods result in spheru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 37 publications
1
18
0
Order By: Relevance
“…While the polymers align in the direction of strain, the local polymer order in the film is kept allowing the films to maintain high quantum efficiency. In fact, the photodetector performance in terms of R , detectivity, and 3 dB cutoff frequency is among the highest reported for all‐polymer photodetectors, and intrinsically polarization‐sensitive organic or inorganic photodetectors . In summary, the demonstrated devices highlight the opportunity of all‐polymer photodetectors to achieve high‐performance intrinsically polarization‐sensitive photodetectors with broad spectral response.…”
Section: Resultsmentioning
confidence: 82%
See 1 more Smart Citation
“…While the polymers align in the direction of strain, the local polymer order in the film is kept allowing the films to maintain high quantum efficiency. In fact, the photodetector performance in terms of R , detectivity, and 3 dB cutoff frequency is among the highest reported for all‐polymer photodetectors, and intrinsically polarization‐sensitive organic or inorganic photodetectors . In summary, the demonstrated devices highlight the opportunity of all‐polymer photodetectors to achieve high‐performance intrinsically polarization‐sensitive photodetectors with broad spectral response.…”
Section: Resultsmentioning
confidence: 82%
“…This feature can be exploited to achieve photodetectors that are polarization sensitive without the need of additional light‐manipulating optics. This reduced complexity simplifies polarization‐sensitive devices, and opens up new opportunities in detector architectures such as polarized detectors in tandem to realize compact coincident polarimeters (polarization state detectors) …”
Section: Introductionmentioning
confidence: 99%
“…The former method would increase the cost and complexity of the system similar to the narrowband photodetectors while the latter one relies on the geometric anisotropy of the materials or the anisotropic crystal structures of the materials and thus can reduce the cost and complexity due to the free of polarizer. Filterless polarization‐sensitive photoresponse has demonstrated in a variety of materials including geometric anisotropic materials such as nanowire, nanobelts, and nanotubes and materials with anisotropic crystal structures such as GeAs, SnS, black phosphorus, barium titanium sulfide, and organic semiconductors …”
Section: Introductionmentioning
confidence: 99%
“…In 2017, they showed that—following the procedure by Müller et al . of adding TCB to the processing solvent—the location of nucleation on the substrate could be controlled by a stream of gas pointing on the film surface, causing the mentioned spot to dry faster and therefore inducing nucleation . For example, by pointing a stream of gas on the substrate surface through a needle during spin coating, a large area covered by only one spherulite could be produced.…”
Section: Spherulites In Semiconducting Semicrystalline Polymer Filmsmentioning
confidence: 99%